Electrically Conductive Aluminum Oxide Thin Film Used As Cobalt Catalyst-Support Layer In Vertically Aligned Carbon Nanotube Growth - Mohd Abid, Mohd Asyadi Azam; Isomura , Kazuki; Ismail, Syahriza; Mohamad, Noraiham; Shimoda, Tatsuya (IOP Publishing, 2015)
-